2010
DOI: 10.1128/jcm.00866-10
|View full text |Cite
|
Sign up to set email alerts
|

Cholera between 1991 and 1997 in Mexico Was Associated with Infection by Classical, El Tor, and El Tor Variants of Vibrio cholerae

Abstract: Vibrio cholerae O1 biotype El Tor (ET), the cause of the current 7th pandemic, has recently been replaced in Asia and Africa by an altered ET biotype possessing cholera toxin (CTX) of the classical (CL) biotype that originally caused the first six pandemics before becoming extinct in the 1980s. Until recently, the ET prototype was the biotype circulating in Peru; a detailed understanding of the evolutionary trend of V. cholerae causing endemic cholera in Latin America is lacking. The present retrospective micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
45
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 32 publications
5
45
0
1
Order By: Relevance
“…All of these assays further confirmed the V. cholerae strains to be toxigenic and as belonging to serogroup O1 . The presence of biotype-specific marker genes, such as rtxC, tcpA ET , rstR ET and ctxB CL , confirmed that the V. cholerae O1 strains causing endemic cholera in Dhaka between 2006 and 2011 were ET but contained the ctxB marker gene of the CL biotype, as reported previously Alam et al, 2010).…”
Section: Discussionsupporting
confidence: 53%
“…All of these assays further confirmed the V. cholerae strains to be toxigenic and as belonging to serogroup O1 . The presence of biotype-specific marker genes, such as rtxC, tcpA ET , rstR ET and ctxB CL , confirmed that the V. cholerae O1 strains causing endemic cholera in Dhaka between 2006 and 2011 were ET but contained the ctxB marker gene of the CL biotype, as reported previously Alam et al, 2010).…”
Section: Discussionsupporting
confidence: 53%
“…Six serologically confirmed O1 strains reacted to monovalent Inaba antiserum and amplified primers for ompW and wbe (Hoshino et al, 1998), but not ctxA, indicating that they were ctx 2 V. cholerae O1. The ctx 2 V. cholerae O1 occurs in the aquatic environment and has been shown to arise following loss of the CTX prophage Alam et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This surmise was probably based on the observation that there had been no sign of cholera in South, Central, or North America for more than a century. Recently, however, V. cholerae El Tor hybrid variant strains were shown to be dominant among V. cholerae CL and ET biotype progenitor strains associated with endemic cholera in Mexico between 1991 and 1997 (2). Although the pre-and post-1991 existence of V. cholerae CL biotype strains along with ET hybrid and prototype ET strains up until 1997 was suggestive of a local environmental reservoir in Mexico (2), little is known about their phenotypic and genetic traits and, more specifically, their ancestry to discern whether the CL biotype strains isolated from endemic cholera in Mexico were evolving locally or were of Asian origin.…”
mentioning
confidence: 99%
“…Recently, however, V. cholerae El Tor hybrid variant strains were shown to be dominant among V. cholerae CL and ET biotype progenitor strains associated with endemic cholera in Mexico between 1991 and 1997 (2). Although the pre-and post-1991 existence of V. cholerae CL biotype strains along with ET hybrid and prototype ET strains up until 1997 was suggestive of a local environmental reservoir in Mexico (2), little is known about their phenotypic and genetic traits and, more specifically, their ancestry to discern whether the CL biotype strains isolated from endemic cholera in Mexico were evolving locally or were of Asian origin. In the present study, comparative phenotypic, molecular, and phylogenetic data related to V. cholerae CL biotype strains isolated in Mexico (n ϭ 6; 1983 to 1997) and Bangladesh (n ϭ 22; 1962 to 1989) have been analyzed, and the results show that the V. cholerae CL biotype strains may have evolved independently in the two geographically distant ecosystems.…”
mentioning
confidence: 99%